2017
DOI: 10.1016/s1470-2045(17)30345-5
|View full text |Cite
|
Sign up to set email alerts
|

European Association for Neuro-Oncology (EANO) guidelines for palliative care in adults with glioma

Abstract: Patients with glioma present with complex palliative care needs throughout their disease trajectory. The life-limiting nature of gliomas and the presence of specific symptoms related to neurological deterioration necessitate an appropriate and early palliative care approach. The multidisciplinary palliative care task force of the European Association of Neuro-Oncology did a systematic review of the available scientific literature to formulate the best possible evidence-based recommendations for the palliative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
184
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(208 citation statements)
references
References 93 publications
5
184
0
3
Order By: Relevance
“…Previous studies reported that gliomas may significantly impair cognitive functions (Derks et al, ; Liu et al, ; Noll et al, ; Pace et al, ; van Kessel, Baumfalk, van Zandvoort, Robe, & Snijders, ). Notably, significant differences were found in math exam test, DSST, mapping test, and similarity test between HCs and in patients with glioma before surgery, which was partially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported that gliomas may significantly impair cognitive functions (Derks et al, ; Liu et al, ; Noll et al, ; Pace et al, ; van Kessel, Baumfalk, van Zandvoort, Robe, & Snijders, ). Notably, significant differences were found in math exam test, DSST, mapping test, and similarity test between HCs and in patients with glioma before surgery, which was partially consistent with previous studies.…”
Section: Discussionmentioning
confidence: 98%
“…The need for supportive‐care interventions—broadly defined in this review as psychosocial/behavioral, pharmacological, complementary, or alternative interventions—to improve HRQoL among brain tumor patients has been emphasized and noted as an important and emerging area . To date, three reviews have considered supportive‐care interventions in patients with brain tumors .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, using a scoring system for mixed methods research and mixed studies reviews, the authors of this review concluded that the majority of the studies that they reviewed only met 33.3/100 of the quality criteria. In 2017, the European Association for Neuro‐Oncology (EANO) published guidelines for palliative care in adults with glioma . These guidelines were developed based on a comprehensive and systematic review of the literature yielding 251 included studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations